A Synopsis of the Report of an Independent Inquiry into the Circumstances of an Incident of Concerted Indiscipline and Fire in Erne House, Maghaberry Prison on 26th April 2015. (2016) - (Prison warden), Spencer, Jerry; Northern Ireland., Prison Service,
No abstract available